Money and Credit in Norway - Christian Kascha (Norges Bank, 2009)
The recent turmoil in the global financial markets raises questions about the nature of the downturn of the Norwegian economy. In particular, are worsening credit market conditions also a leading cause of the Norwegian 2009 recession? In order to shed some light on these questions, this note investigates the historical behavior of different money and credit series and their relationship with real economic activity as measured by growth in GDP Mainland Norway.
hdl:11250/2507914
Keywords: 330